The Holobiontic Figure: Narrative Complexities of Holobiont Characters in Joan Slonczewski’s Brain Plague - Brandt Teun Joshua (Open Cultural Studies, 2023)
In this article, I propose to consider the holobiontic figure as a starting point for examining how literary narratives represent the holobiosis paradigm and its impact on narrative structure. A body of recent science fiction works is challenging the long-standing narrative of microbes as “bad germs” and the ever-evolving plot of the pandemic apocalypse by depicting humans as intricately interwoven with their microbial symbionts. The notion of the holobiontic figure, in this regard, serves as a point of reference for characters in the process of recognising themselves as holobionts. This article conducts a detailed exploration of the narratological aspects of the holobiontic figure through a reading of Joan Slonczewski’s novel Brain Plague. On the basis of this novel, two essential characteristics of the holobiontic figure are proposed and discussed: multiscalarity and multi-agency. With this, the article aims to provide answers to the question what happens when the scientific concept leaves the scientific discourse and moves between materials: how does it relate to the social world, what structures does it contest, and what conflicts does it provoke?